Cervical mucus antibodies against human papillomavirus type 16, 18, and 33 capsids in relation to presence of viral DNA. - Wang, Z (1996)
To investigate whether cervical mucus antibodies against human papillomavirus (HPV) capsids are associated with the detection of HPV DNA or HPV-related cytological diagnoses, 611 samples of cervical secretions from 359 women referred to a colposcopy clinic were tested by an enzyme-linked immunosorbent assay for the presence of immunoglobulin A (IgA) antibodies against HPV capsids of HPV type 16, 18, or 33 and for the presence of cervical HPV DNA by PCR. Among subjects with at least one cervical sample positive for HPV type 16 (HPV-16) DNA, 28.1% also had at least one HPV-16 IgA-positive cervical sample (odds ratio [OR] = 2.9; P = 0.0003). IgA to HPV-18 was also more common among HPV-18 DNA-positive subjects (OR = 3.1; P = 0.0325) and IgA to HPV-33 was more common among HPV-33 DNA-positive subjects (OR = 4.2; P = 0.0023). Cervical IgA antibodies to HPV-16 were also more common among patients with cervical intraepithelial neoplasia, particularly among patients with cervical intraepithelial neoplasia grade I (P < 0.0005). The data indicate that an HPV type-restricted IgA antibody response against HPV capsids is detectable in cervical mucus and is associated with a concomitant cervical HPV infection.